Processos educativos e memórias de mulheres em processo de envelhecimento que vivem em um abrigo e participam de uma tertúlia musical dialógica - Silva, Sara Regina Moreira da (Universidade Federal de São Carlos, 2008)
The present investigation has as objectives describe the processes of aging in capitalist society and the need of humanization of the relations in this process; analyze the educational processes and memories from musical from musical living on which possibility musical hearing of classics and the interaction with the music and among people; evaluate the impact, limits and possibilities of a dialogical musical activity in the retirement home for women context in aging process, trying to understand how this activity caused impact in the participating women s routine, identifying after these analyzes the work contribution to the society in general, to education e to the musical education. To achieve these objectives, we carried out in the retirement home the activity named Dialogical Musical Tertulia, dialogue activity with regard to the classic music listening. Implying classics as, in this research, the musical works that crossed the time, taking part of a culture s tradition and respecting the coherence and strict the origin of musical style. In the activity, these women could share and connect the songs listened and their life experiences telling their memories. Participating observations were carried out, notes in field diaries and interviews with people who take care in the retirement home and some participating women of the activity. The collected data was organized as dialogical learning dynamic, the processes if solitude among the participating women; the creation of the meaning in an activity which gather to share the memories and the living of music; the attitudes changes and the transformation occurred from the verbal and nonverbal interaction, the musical behavior shown by the participants demonstrating the relations established with the music and educational processes generated from these behaviors, including certain musical learning; the relation between music and memory, memory and society and the importance of the memory to the people in the aging process and even old age, the life in the retirement home and the classics in the tertulia through the participating women s vision. The research also tried to understand how much the dialogical musical appreciation, considering the levels sensitive and expressive, the interaction and the memory task contributed with the enlargement of the educational relations in the musical education and among the women. All the approached aspects in the research still collaborate with the old age life quality improvement. Finally we could observe the contributions of this work to the Education field, the Musical Education and to the society in general, describing final considerations that pointed ways in the search to overcome of the oppressions situations lived at the old age, bigger search after cultural educational actions carried out in the investigation time through the interaction with music and among people in the Dialogical Musical Tertulia activity.
Keywords: Educação de jovens e adultos; Educação musical; Práticas sociais; Envelhecimento humano - aspectos sociais; Social practice; Musical education; Youngsters and adult education; CIENCIAS HUMANAS::EDUCACAO